Cyclosporine A and autologous serum efficacy for treatment of vernal keratoconjunctivitis - Ahmed Esmail; Ahmed O. Hashem; Mohammed Elashri; Mohamed Ahmed Hafez Ibrahim (Journal of the Egyptian Ophthalmological Society)
Purpose To compare the effectiveness of using Cyclosporine A (CsA) eye drops with a concentration of 0.05% alone versus using eye drops containing both CsA of 0.05% concentration combined with autologous serum (AS) of 20% used together for treating vernal keratoconjunctivitis (VKC) which were moderate to severe. Methods A prospective comparative noninterventional case series was carried out at the Ophthalmology Department at Kafrelsheik University, involving 40 individual patients with moderate to severe VKC sorted into two groups; 20 patients using CsA 0.05% eye drops as group A and 20 patients in group B using eye drops of CsA 0.05% combined with AS eye drop of 20% concentration for treating VKC for 12 weeks, 4 times daily. Results According to the scores recorded for symptoms and signs, the difference detected statistically was of no significance among the two involved study groups as regards the baseline score (P=0.783, and 0.137, respectively). While the scores reported for the symptoms and signs were statistically lower significantly among group B other than observed among group A as determined at the 4th week (P=0.015, and 0.004, respectively), 8th week (P<0.001, for both), and 12th week (P=0.001, and 0.002, respectively). Regarding side effects of treatment, 12 patients had a burning sensation, eight of them in group A and four patients in group B, with not reach to significant level between the studied groups during the follow-up visits (P=0.382) Conclusions We concluded a higher efficacy of using combined eye drops of CsA 0.05% and AS 20% for treating VKC than CsA 0.05% eye drops alone.